Trade Openness and Health Financing in Sub-Saharan Africa - (:unkn) unknown (My University, 2024)
In 2019, the Covid-19 health crisis profoundly disrupted the global economy, particularly international trade, due to restrictive measures that hindered local production and exchanges. This situation highlighted the importance of an effective healthcare system for economic stability, a consideration that is especially crucial for developing countries like those in Sub-Saharan Africa, where healthcare infrastructure is insufficient. A large-scale pandemic in this region could severely impact trade and investment. Therefore, it is essential to develop robust healthcare infrastructure to enhance economic resilience in the face of future crises. This thesis examines the impact of health crises on the trade of Sub-Saharan African countries. It highlights the beneficial effects of improving healthcare systems on the attractiveness of foreign direct investment and addresses the efficiency of public health systems. The thesis is organized into three chapters, each aimed at answering the following questions, respectively: How do epidemic-related restrictions affect bilateral trade between infected countries and their partners? What influence does a high-performance healthcare system have on the attractiveness of foreign direct investment? How can public health expenditures be efficiently managed in a context of budgetary constraints? Drawing on the case of the Ebola crisis using a gravity model, the first chapter highlights the negative impact of restrictions related to this epidemic on the exports of the affected West African countries, particularly on fresh products. Additionally, the findings show that when an epidemic is localized in a specific group of countries, the restrictions primarily affect exports without significantly impacting imports. These results underscore the detrimental effects on international trade of excessive restrictions that do not adhere to the World Health Organization's recommendations during health crises. Using a fixed-effects mod
Keywords: African Research